Covid-19 in Nepal: Governance and its Implication on Public Health Measures - sherpa, Ang Tshering Lama; Sherpa, Tenzing Lhamo (Nepalese Medical Journal, 2021)
COVID-19, the pandemic caused by SARS- CoV-2 has affected more than 220 countries including Nepal, costing millions of lives around the globe. Despite the government’s effort to contain the virus by initiating several public health measures, the exponential growth of COVID-19 cases has been noted in due course. Our review is focused on preventive health measures and the role of government in implementation, in the context of Nepal. We found that while the government did enact some policy and guidelines in response to COVID-19, the response was lacking in timely execution, coordination and monitoring, and was not in compliance with human rights principles.